1989
DOI: 10.1111/j.1574-6968.1989.tb03640.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural alterations inSaccharomyces cerevisiaecells in association with elevated temperature-induced autolysis

Abstract: By means of the freeze‐etching technique ultrastructural alterations in Saccharomyces cerevisiae cells undergoing autolysis at elevated temperature were studied. Wall surfaces of intact cells were smooth. During autolysis wall surfaces became rough with granules of 20–40 nm diameter. This alteration occurred after extensive disintegration of cytoplasmic organelles and after functional and ultrastructural impairments of the plasma membrane, but well before the rupture of the plasma membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
0
3
1
Order By: Relevance
“…As mentioned above, structural alterations were hardly detectable either in cell wall or in cellular membranes after growth of yeast cells at elevated temperatures, in contrast to the previous observations 6 ) which found marked changes during incubation of the cells for autolysis. The intactness of cell structure during cultivation at elevated temperatures was consistent with the fact that few cellular materials were released from the cells before incubation for autolysis ( Fig.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…As mentioned above, structural alterations were hardly detectable either in cell wall or in cellular membranes after growth of yeast cells at elevated temperatures, in contrast to the previous observations 6 ) which found marked changes during incubation of the cells for autolysis. The intactness of cell structure during cultivation at elevated temperatures was consistent with the fact that few cellular materials were released from the cells before incubation for autolysis ( Fig.…”
Section: Discussioncontrasting
confidence: 54%
“…The ultrastructural alterations in cell wall and in cellular membranes (the plasma membrane and intracellular membranes) were investigated with an electron microscope by freeze-etching technique as described previously. 6) Estimation of susceptibility of yeast cells to cell wall lytic enzyme. The reaction mixture (10 ml) contained about 60 mg dry wt.…”
Section: Observations Of Cells By Light and Electron Microscopymentioning
confidence: 99%
“…2). This extensive desintegration of cytoplasmic organelles is equivalent to that described during autolysis of other fungi with micelial cells, but in yeast cells few ultrastructural studies about autolysis have been reported [23].…”
Section: Effect Of 2a Pr° Expression On Yeast Intracellular Morphologymentioning
confidence: 60%
“…However, the possibility that HIV-1 PR might be directly involved in cell wall degradation seems very unlikely. The cell wall affords mechanical protection to yeast cells against osmotic lysis (45,46). Indeed, growth of lytic strains with mutations in genes involved in cell wall integrity can be effectively restored by osmotic stabilizers (41).…”
Section: Cell Lysis Induced By Hiv-1 Pr Expressed In the Context Of Tmentioning
confidence: 99%